Directly probing the effect of the solvent on a catalyst electronic environment using X-ray photoelectron spectroscopy1. Issue 45 (20th May 2015) - Men, Shuang; Lovelock, Kevin R. J.; Licence, Peter
<x xml:space="preserve">Abstract</x> The anion of an ionic liquid can significantly influence the electronic environment of a metal centre, and thus impact upon reaction performance in a model Suzuki cross coupling reaction.